Teachers’ Teaching Styles, Students’ Learning Styles and Level of Competencies of Children With Special Needs in Secondary Public Schools of Zone Iv, Division of Zambales - Rosal, Mark Anthony Mendoza; Echaure, Jessie S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The focal objective of this study was to examine the various teaching styles, learning styles, as well as the level of competencies of children with special needs in the Secondary Public schools of Zone IV, Division of Zambales during School Year 2018-2019.The aforesaid study applied quantitative descriptive research design with questionnaire as the main instrument in gathering from teacher and students with special needs. Moreover, the study revealed that the Special Education (SPED) teacher is typically female, in her early adulthood, married, master’s degree holders with almost a decade in the teaching service and few numbers of attendance to seminars and training. The Special Education (SPED) student learning style was “visual learning”. There is substantial difference on competence level when congregated conferring to grade level, and age. There is significant difference on the learning styles of SPED students when grouped according to grade level, and age profile. There is significant difference on the teaching styles when clustered according to sex, age, highest educational attainment, length of years in service and number of trainings. Finally, the researcher recommended that if budget warrants, the school administrators should prioritize sending teachers handling SPED class for training and seminars to keep abreast on the new trends in teaching physically handicap students; hiring legitimate and experts in SPED program should be hired for better implementation of the program is strongly encourage; to administer/conduct a parallel or similar study in order to validate and confirm the findings attained in the study.